The dynamic crustal and mantle structure around the afar triple junction - Gauntlett, M (2024)
The Afar Triple Junction marks the confluence of the Red Sea rift, the Gulf of Aden and the East African Rift System. The Afro-Arabian Rift System (AARS) encompasses these three rifts, each in a different stage of continental breakup. I investigate the crust and mantle beneath this complex tectonic region using three different seismological techniques.